2001
DOI: 10.1074/jbc.m010952200
|View full text |Cite
|
Sign up to set email alerts
|

Rpb4, a Non-essential Subunit of Core RNA Polymerase II ofSaccharomyces cerevisiae Is Important for Activated Transcription of a Subset of Genes

Abstract: A major role in the regulation of eukaryotic protein-coding genes is played by the gene-specific transcriptional regulators, which recruit the RNA polymerase II holoenzyme to the specific promoter. Several components of the mediator complex within the holoenzyme also have been shown to affect activation of different subsets of genes. Only recently has it been suggested that besides the largest subunit of RNA polymerase II, smaller subunits like Rpb3 and Rpb5 may have regulatory roles in expression of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
6
38
0
Order By: Relevance
“…Studies using promoter reporter constructs have also shown that various unrelated genes are affected to different extents in rpb4⌬ (8). On the other hand, the stress-related phenotypes of rpb4⌬ cells like temperature sensitivity and lethality during the stationary phase point toward a stress-specific role for RPB4 in transcription.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies using promoter reporter constructs have also shown that various unrelated genes are affected to different extents in rpb4⌬ (8). On the other hand, the stress-related phenotypes of rpb4⌬ cells like temperature sensitivity and lethality during the stationary phase point toward a stress-specific role for RPB4 in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the activation defect of rpb4⌬ strain can be partially rescued by overexpression of the cognate transcriptional activator (8). Msn2 (transcriptional activator in heat shock response) and some other proteins (that are not transcriptional activators) have been shown to partially rescue the temperature sensitivity of rpb4⌬ cells (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, Rpb4 (Kimura et al, 2001) and Rpb7 (Khazak et al, 1995;Na et al, 2003) can be found in the cytoplasm with Rpb4 mediating RNA export from the nucleus under stress conditions (Farago et al, 2003) and both Rpb4 and Rpb7 are involved in selective mRNA decay (Lotan et al, 2005;Goler-Baron et al, 2008). In terms of their biological roles, while scRpb4 and scRpb7 may not be identical (scRpb4 is conditional (Woychik and Young, 1989) and scRpb7 is essential (McKune et al, 1993)) both proteins are nonetheless involved in particular stress responses (Choder and Young, 1993;Sheffer et al, 1999;Maillet et al, 1999;Pillai et al, 2001) and are implicated in morphological changes that accompany nutrient starvation (Khazak et al, 1995;Pillai et al, 2003). Consistent with the conditional nature of scRpb4, global gene expression profiling in yeast indicates that a limited number of genes (~2% of the genome) are affected by Rpb4 (Pillai et al, 2003), although other evidence points to a more global effect (Miyao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%